46th AIAA/ASME/ASCE/AHS/ASC Structures, Structural Dynamics and Materials Conference 2005
DOI: 10.2514/6.2005-2175
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Aeroelastic and Aerothermoelastic Behavior in Hypersonic Flow

Abstract: The aeroelastic and aerothermoelastic behavior of three-dimensional configurations in hypersonic flow regime are studied. The aeroelastic behavior of a low aspect ratio wing, representative of a fin or control surface on a generic hypersonic vehicle, is examined using third order piston theory, Euler and Navier-Stokes aerodynamics. The sensitivity of the aeroelastic behavior generated using Euler and Navier-Stokes aerodynamics to parameters governing temporal accuracy is also examined. Also, a refined aerother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 52 publications
0
33
0
Order By: Relevance
“…In practice, control surfaces on hypersonic vehicles will be required to have a small angle of attack to produce the necessary control forces. It has been shown [80,81] that for the unheated case, a small angle of attack will not significantly modify the flutter boundary of a two-dimensional typical section. However, angle of attack is important when aerodynamic heating is considered, because it introduces asymmetry in the temperature distribution between the upper and lower surfaces of a wing.…”
Section: Effect Of Aerodynamic Heating On the Free-vibration Charactementioning
confidence: 99%
“…In practice, control surfaces on hypersonic vehicles will be required to have a small angle of attack to produce the necessary control forces. It has been shown [80,81] that for the unheated case, a small angle of attack will not significantly modify the flutter boundary of a two-dimensional typical section. However, angle of attack is important when aerodynamic heating is considered, because it introduces asymmetry in the temperature distribution between the upper and lower surfaces of a wing.…”
Section: Effect Of Aerodynamic Heating On the Free-vibration Charactementioning
confidence: 99%
“…Historically, the structural behavior to these different sources has been considered separately. In the first class of problems, the quasi-static panel response (Kontinos, 1997;Culler et al, 2009), and dynamic instabilities (McNamara et al, 2005;Mei et al, 1999;Culler et al, 2009) has been studied by modeling the boundary layer loads and other external acoustic excitations: (1) as a random in time, and uniform in space acoustic load (Przekop and Rizzi, 2006;Spottswood et al, 2010), (2) using semi-empirical models (Maestrello, 1969;Hwang et al, 2009;Hambric et al, 2004;Coe and Chyu, 1972;Wu and Maestrello, 1995), and (3) using high-fidelity Computational Fluid Dynamics (CFD) simulations (Frendi, 1997(Frendi, , 2004. There are limitations of each of these approaches.…”
mentioning
confidence: 99%
“…The inclusion of heating was found to significantly change the aeroelastic response of the wing, as it resulted in flutter in conditions that were aeroelastically stable for the cold wing. A number of steady aerodynamic models have been coupled with the structural dynamics, namely piston theory, Euler and Navier-Stokes aerodynamics [16,23,24]. These studies have verified the use of third order piston theory as an accurate model of the aerodynamics in hypersonic flight.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the early research was instrumental in providing the basis for the aerothermoelastic design of the X-15 and the space shuttle [3][4][5], the current focus is on the development of hypersonic technologies for next-generation reusable launch vehicles and hypersonic cruise vehicles [6][7][8]. Current research includes: development of reduced order models for aerothermoelastic systems [9,10], structural optimisation [11], uncertainty propagation [12,13], coupling CFD with aerothermoelastic models [14], two-dimensional nonlinear flutter models [15] and three-dimensional flutter models [16]. This work has shown that the dynamic behaviour of the structure under the harsh thermal environment must be investigated for hypersonic aircraft to become a reality.…”
Section: Introductionmentioning
confidence: 99%